PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP FINANCIAL DISTRESS BADAN USAHA MILIK NEGARA DAN SWASTA (Studi Empiris terhadap Perusahaan Manufaktur di Indonesia yang Terdaftar pada BEI Tahun 2018-2022) - Saragih, Alfanadia Putri G.; Mutmainah, Siti (Diponegoro Journal of Accounting, 2024)
The purpose of this study is to examine the effect of corporate social responsibility (CSR) and its relation to financial distress using stakeholder and signal theory through observation of manufacturing enterprises listed in Indonesia Stock Exchange (IDX) from 2018 to 2022. This study uses Altman Z-Score, a bankruptcy ratio, as a measure of financial distress and CSR monetary spending ratio (MSR) as a measure of CSR. Using purposive sampling technique, 152 enterprises were obtained as sample, consisting of 142 state-owned enterprises and 10 non-state-owned enterprises. The results of this study states that CSR doesn’t show a significant effect on financial distress of state-owned enterprise nor it is on non-state-owned enterprise. However, a more significant effect was seen on non-state-owned enterprise though state-owned enterprise were the one that are more motivated doing CSR.